Hepatic Steatosis Has No Effect in Diagnosis Accuracy of LI‐RADS v2018 Categorization of Hepatocellular Carcinoma in MR Imaging - Yao, Shan; Wei, Yi; Ye, Zheng; Chen, Jie; Duan, Ting; Zhang, Zhen; Song, Bin (Journal of magnetic resonance imaging, 2024)
Background In clinical practice, hepatocellular carcinoma (HCC) is widely diagnosed by using MRI, however, whether the imaging features are affected by hepatic steatosis (HS) is still unknown. Purpose To investigate and compare the differences in HCC related imaging features between with‐ and without‐HS groups, and to further determine whether HS affects the diagnosis accuracy of Liver Imaging Reporting and Data System (LI‐RADS) v2018 of HCC in MRI. Study Type Prospective. Subjects One hundred and seventy‐one patients (mean age, 52 ± 11 years; range, 26–83 years) including 137 men and 34 women. Field Strength/Sequence 3.0 T, gradient echo (GRE). Assessment Subjects were classified as HS and non‐HS groups according to MRI‐proton density fat‐fraction (PDFF). HS was defined as MRI‐PDFF >5.6%. Three radiologists accessed HCC features and assigned LI‐RADS categories in MRI independently based on LI‐RADS v2018. Frequencies of HCC major features and LR categorization assignment between the two groups as well as interobserver agreement between the two radiologists were assessed. Statistical Tests Unpaired t‐test, Chi‐square test, Fisher's exact test, kappa statistic, intraclass correlation coefficient (ICC). A two‐sided P value <0.05 was considered as statistically significant. Results Major features including arterial hyperenhancement (APHE), enhancing “capsule” and nonperipheral “washout” observed between HS and non‐HS groups were not significantly different (78.95% vs.78.62%, P = 0.866; 57.89% vs.52.98%, P = 0.483; and 75% vs.81.46%, P = 0.257, respectively), and the assessment of observation size showed a borderline difference (P = 0.059). No significant difference in LR‐5 assignment between the two groups (69.74% vs. 72.85% for reader 1, P = 0.641; 71.05% vs. 72.19% for reader 2, P = 0.877). Interobserver agreement between the two radiologists showed almost perfect in LR‐5 assignment (κ = 0.869) and size observation (ICC = 0.997). Data Conclusion The diagnosis of HCC based on LI‐RADS v2018 in MRI is of comparable performance regardless of HS, in which there is no significant difference in either the major imaging features or LR categorization. Level of Evidence: 2 Technical Efficacy Stage: 2